Sber dat a Urazový registr Ceské republiky - Gál, P; Plánka, L; Starý, D; Trlica, J; Dedek, T (Rozhledy v chirurgii, 2006)
INTRODUCTION: A trauma registry is an integral part of any thorough traumatological care conception. The essential task of such a data collection is to provide complex information on conditions, treatment, outcomes and trauma treatment costs, considering a region or other registered part of, usually, a state entity. MATERIAL, METHODOLOGY: Registration of individual trauma characteristics throughout the state territory is a prerequisite for creating a data set, providing information for making valid conclusions applicable for all ranges of human activity. The trauma registry outputs are essential for traffic institutions, police, commercial inspection, commercial and health insurance companies, hospitals, etc. With respect to traffic problematics, the trauma registry plays a significant role in pointing out the most risk places in the region, in assessing the traffic type and use of protective tools. Furthermore, it facilitates exact aiming of preventive and corrective measures. CURRENT CONDITION: Current legislation does not require reporting data to the trauma database, insufficient data are provided by UZIS only. Our Clinic of Paediatric Surgery, Orthopaedics and Traumatology iniciated a model version of the Czech Republic National Trauma Registry. Our activities were approved by and supported by the Society of Traumatologic Surgery. It is a question of time, when sufficient pressure is exerted and the trauma registry becomes an integral part of the traumatological care in the Czech Republic.
Keywords: Accidents, Traffic; Registries; Česká republika; registrace; lidé; rány a poranění; Data Collection; Wounds and Injuries; Czech Republic; sběr dat; dopravní nehody; Humans